POTENSI DAN PENGEMASAN PAKET EKOWISATA DI KABUPATEN BERAU PROVINSI KALIMANTAN TIMUR - Fariz, Aji Muhammad; Sudana, I Putu; Dewi, N.G.A.S. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 9 No 1 (2021): Jurnal IPTA (July 2021)DO - 10.24843/IPTA.2021.v09.i01.p03, 2021)
This research was conducted to determine the potential of ecotourism in Berau Regency, East Kalimantan Province so that it can be packaged into an ecotourism package that covers the whole area of Berau Regencey starting from the urban zone, the inland zone and the water zone. This Research was conducted in Berau Regency because Berau Regency has 159 tourist attractions and also its location is close to the location of the new capital. The ecotourism package packaging made in this study is based on the lack of variety of products and tour packages circulating in Berau Regency so that this research is expected to add variety as well as introduce new potentials that can be found in Berau Regency. Data collection techniques used in this study are in-depth interviews, observation, documentation, and literature study. After conducting research in Berau Regency, there are 17 ecoutourism potentials which can be packaged into 4 kinds of ecoutourism packgaes, with details of theree full-day ecotourism packages and one 2-day 1 night ecoutourism packages and the ecotourism package itinerary in this study is made in the form of descriptions, tables, and graphs as well as the type of ecotourism package in this study is ready made tour. The titles of  the ecotourism packages in this study are (1) Berau Culture and City Tour, (2) Berau Mangrove and Sangalaki Island Tour, (3) Orangutan University and Merabu Forest Tour, (2) Mirror Lake and Whale Shark Tour.